If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + 6 + -5n = -12 + -6n Reorder the terms: 6 + 5n + -5n = -12 + -6n Combine like terms: 5n + -5n = 0 6 + 0 = -12 + -6n 6 = -12 + -6n Solving 6 = -12 + -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. 6 + 6n = -12 + -6n + 6n Combine like terms: -6n + 6n = 0 6 + 6n = -12 + 0 6 + 6n = -12 Add '-6' to each side of the equation. 6 + -6 + 6n = -12 + -6 Combine like terms: 6 + -6 = 0 0 + 6n = -12 + -6 6n = -12 + -6 Combine like terms: -12 + -6 = -18 6n = -18 Divide each side by '6'. n = -3 Simplifying n = -3
| 7sinx+11=5 | | 2=14-2p | | 1+3n=9+4n | | x^5-10x^3+25x=0 | | c=6(x+2y)+18x | | -6+n=-2n+6 | | 1.5d+9.25=7+2.25d | | 2-r=r-7-4-3 | | -1414x+14=8 | | 2n-12=4 | | 10/16x6/14 | | 1-4v=9-v-v | | 9(2n+7)=11(n+14) | | (3-5i)(6+3i)= | | 10/16*6/14= | | -2-3X+x=6 | | x^2+8x+16=6x+2 | | n^5=1024 | | -2-8x+1=-9 | | 3x+2x-15=15 | | -1=1-7v+6v | | f(8)=4x+6 | | 3(m+5)=4(m-3) | | F(x)=8x-3/5 | | K(x)=x^2-2x+8 | | 16x-(-2x*2x)/2 | | X-(0.36X)=175 | | 0=-3x^2+228x-3900 | | 4x+(46-x)(-1)=79 | | 2x+15=3x-7 | | 3cot+3=0 | | 1/2cosx=0 |